Factors Affecting Financial Behavior of Micro, Small and Medium Enterprises (MSMEs): The Role of Financial Inclusion, Financial Literacy and Financial Technology - Azizah, Farinda Hauna; Innayah, Maulida Nurul; Tubastuvi, Naelati; Aryoko, Yudhistira Pradhipta (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The research examines the factors that influence the financial behaviour of micro, small and medium-sized enterprises (MSMEs), focusing on the roles of financial inclusion, financial literacy, and financial technology, framed within the Theory of Planned Behavior. The population for this research consisted of 89,553 MSME players, with a sampling technique utilizing the Slovin formula to achieve a sample size of 142 respondents. Using a mixed-methods approach, the research combines quantitative surveys of MSME owners. The findings reveal that financial inclusion significantly enhances access to credit and financial services, thereby improving the financial behavior of MSMEs. Additionally, higher levels of financial literacy correlate with better financial management practices, leading to increased profitability and sustainability. The study also highlights the transformative impact of financial technology, which facilitates easier access to financial resources and enhances operational efficiency. The results indicate that financial inclusion, financial literacy, and financial technology have a positive and significant effect on the financial behavior of MSMEs. This suggests that targeted interventions in these areas could foster greater economic resilience and growth within this vital sector.